ETHNOCONFESSIONAL POLICY OF INDEPENDENT UZBEKISTAN AND JEWISH COMMUNITIES - Jamoliddin Karimov (Galaxy International Interdisciplinary Research Journal, 2022)
Significant work is being done in Uzbekistan to ensure harmony and tolerance between people of different nationalities, ethnic groups, and religions with ancient lands. The unanimous adoption of the resolution "Enlightenment and Religious Tolerance" put forward by Uzbekistan by the UN member states is practical proof of this idea. An important task is to further strengthen inter-ethnic harmony and inter-religious tolerance on human rights and religious freedom in our country.The article analyzes the work being done in Uzbekistan on ethno-confessional policy, interethnic harmony, and religious tolerance. In addition, the article also covers information on the history of the new era of Bukhara Jews, the activities of synagogues, and Jewish national centers.